Iz zala Konstitutsionnogo suda . Iz zala Konstitutsionnogo suda . From the Constitutional Court . Из зала Конституционного суда - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The case of the constitutionality of the actions of the Communist Party of the Soviet Union (continued) Featured in the program: Rakhmilovich, Viktor Abramovich (Lawyer) Дело о конституционности действий коммунистической партии Советского Союза (продолжение). В программе участвуют: Рахмилович, Виктор Абрамович (Юрист)